(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
Many scientific studies consist of practical parts. This article is about how to get information about the results by saving money and time in machining. It is envisaged to use computing systems and programs to achieve these results. This method is used in some processes in the manufacture of bearing rings.